Integrating Live Gifting Psychology and Behavioral Accounting: Internal Control and Financial Reporting Implications for Virtual Assets - Aulia Rahmadiani Negoro; Ahmad Ainul Yaqin; Noor Bekti Negoro (Jurnal Akuntansi, 2026)
This study synthesizes the explosive growth of live streaming platforms, which has given rise to a new digital economic phenomenon: live gifting. This mechanism allows users to purchase and donate virtual assets to streamers, creating revenue streams worth billions of dollars. The study aims to bridge two distinct academic conversations that have hitherto run in parallel. The first corridor examines the psychological drivers and platform design behind gifting behavior, while the second investigates the accounting, internal control, and financial reporting challenges posed by virtual asset transactions. An integrative gap exists between these perspectives. Studies in information systems and marketing have extensively mapped user motivations and gamification features but often overlook accountability implications, whereas accounting literature tends to address technical issues in isolation, without considering the behavioral drivers of transactions. This study proposes behavioral accounting as a critical integrative lens. Its central argument posits that the psychological biases and social dynamics exploited by platform design (front-end) have direct implications for fraud risk, compliance, and the effectiveness of internal control systems (back-end). The synthesis concludes that a behaviorally informed approach is essential for developing robust control frameworks, relevant accounting standards, and holistic future research agendas within the live gifting ecosystem. At the practical level, the findings imply that platform operators, regulators, and auditors must explicitly incorporate user psychology and choice architecture into the design of internal controls, regulatory standards, and audit procedures, so that governance of virtual assets aligns with how gifting behavior is actually generated and amplified in real-time.